Negative campaigning and electoral mobilization: empirical evidence from German state elections - Jürgen Maier; Sebastian Stier; Mona Dian (Political Research Exchange)
Recent research has been inconclusive about the systemic effects of negative campaigning. The available studies, most of which focus on the United States, either conclude that attack behavior decreases turnout, increases turnout, or has no effect on turnout. This study analyzes the relation between negative campaigning and turnout at the constituency level in 13 German state elections in 2021 and 2024. Based on a triangulation of data from the state returning officers and candidate surveys we show that an overall negative tone of the campaign stimulates voter participation; the predicted difference in turnout between a constituency reporting a low and a constituency reporting a high level of negativity is 2.5 percentage points for the overall campaign and 3.3 percentage points for the candidates’ attack behavior at the constituency level. We conclude that the specific effect of negative campaigning on turnout depends on the level of communication.